2002
DOI: 10.1186/cc1466
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: RSV = respiratory syncytial virus; t PTEF /t E = exhaled time to reach peak expiratory flow as a fraction of total expiratory time; V maxFRC = maximal flow at functional residual capacity produced by forced expiration as a result of a rapid chest compression; V PTEF /V E = tidal volume exhaled at peak tidal expiratory flow as a fraction of total tidal volume.Available online http://ccforum.com/content/6/2/111In this issue of Critical Care, Totapally and colleagues [1] evaluate the effect of albuterol on tidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In a recent review, 9 of 12 randomized controlled trials showed that bronchodilators had no effect [9]. In studies suggesting that β 2 -agonists are effective, conclusions are based on improvement in clinical scores but generally do not show any effect on duration of hospitalization similar to our study.…”
Section: Discussionsupporting
confidence: 75%
“…In a recent review, 9 of 12 randomized controlled trials showed that bronchodilators had no effect [9]. In studies suggesting that β 2 -agonists are effective, conclusions are based on improvement in clinical scores but generally do not show any effect on duration of hospitalization similar to our study.…”
Section: Discussionsupporting
confidence: 75%
“…69,70 Given the high costs and uncertain benefit of this therapy, bronchodilators are not recommended for routine management of first time wheezers. In children with established asthma, bronchodilators are first-line therapy for acute respiratory symptoms whether or not viruses are the cause.…”
Section: Implications For Treatmentmentioning
confidence: 99%